In Search of the Missing Resource Curse - Lederman, Daniel; Maloney, William F. (World Bank, Washington, DC, 2012)
The debate over the curse of natural resources has haunted developing countries for decades if not centuries. A review of existing empirical evidence suggests that the curse remains elusive. The fragile negative effect of natural resources on economic growth might be due to international heterogeneity in the effects of natural resources on economic growth, to the use of weak indicators of natural resources that might be unrelated to relative natural-resource endowments, or to the inability of econometric analysis based on international data to capture historical processes. This paper defends an empirical proxy for relative abundance of natural resources, which is based on standard growth theory. In turn, various econometric estimations are hopelessly deployed in the search for the missing resource curse. Some evidence suggests that natural resources might have large positive effects whose true magnitude remains unknown due to unresolved econometric issues.